The Bento book : beauty and simplicity in digital organization - Feiler, Jesse (Que, 2009)
Bento is the best way to organize your life. Your contacts, events, tasks, projects, stuff, everything. This book makes Bento even better (and even easier). Learn how to use everything that's built into Bento ... and extend Bento to do even more.